The potential mechanistic insights and future implications for the effect of prebiotics on poultry performance, gut microbiome, and intestinal morphology - Yaqoob, M.U.; El-Hack, M.E. Abd; Hassan, F.; El-Saadony, M.T.; Khafaga, A.F.; Batiha, G.E.; Yehia, N.; Elnesr, S.S.; Alagawany, M.; El-Tarabily, K.A.; Wang, M. (Poultry Science, 2021)
Prebiotics may modify the biological processes in the chickens' gastrointestinal tract to improve poultry performance and health. Prebiotics are natural feed additives that offer many economic advantages by decreasing mortality rates, increasing growth rates, and improving birds' feed efficiency. Prebiotic action potentially affects the degradation of indigestible dietary compounds, the synthesis of nitrogen components and vitamins, and simplifies the removal of undesirable elements in the diet. Prebiotics could also induce desirable gut microbiome modifications and affect host metabolism and immune health. It is worth mentioning that gut bacteria metabolize the prebiotic compounds into organic compounds that the host can subsequently use. It is important to limit the concept of prebiotics to compounds that influence the metabolism of resident microorganisms. Any medicinal component or feed ingredient beneficial to the intestinal microecosystem can be considered a prebiotic. In this review, the impacts of prebiotics on the gut microbiome and physiological structure are discussed, emphasizing the poultry's growth performance. The current review will highlight the knowledge gaps in this area and future research directions.